QUALITY OF LIFE OF PATIENTS TREATED BY VALVE-SPARING AORTIC ROOT REPLACEMENT - Ihor O. Stetsyuk; Borys M. Todurov; Oleg V. Zelenchuk; Liubov R. Stetsiuk; Igor Yu. Mokryk; Vsevolod I. Zaviiskyi (Клінічна та профілактична медицина, 2024)
The aim. To determine the effectiveness of David valve-preserving operation in comparison with Bentall operation based on the analysis of patients' quality of life after operations.